Large-scale mapping using UAV-based oblique photogrammetry - Q. Yuan (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Tilt photogrammetry technology breaks through the limitation of orthorectified images that can only be captured from a vertical angle, by carrying multiple sensors to capture images from different angles such as one vertical and multiple tilts. This can obtain higher resolution, larger field of view angle, and more detailed ground information data than traditional methods. In the image acquisition stage, onboard sensors record parameters such as altitude, speed, heading, lateral overlap, and coordinates, and embed geographic image information to enable real-time recording of aircraft attitude parameters with the image data. In the processing of this study, oblique photogrammetry technology was used to obtain image data of the measured area, and GNSS-RTK and IMU systems were used to assist in obtaining external azimuth elements. Meanwhile, the experiment completed route planning, drone assembly, parameter setting, image control scheme design, and measurement. Complete the steps including photo quality inspection, image control point selection and editing, and aerial triangulation calculation. Finally, this study completed the 3D model reconstruction of the measurement area, and 4D product production includes DLG, DOM, and DEM. The quantitative accuracy analysis and visual representation confirmed that the research result meets the requirements of 1:500 scale mapping, and the 3D model can accurately express the information of physical objects.